Penerapan Layanan Bimbingan dan Konseling pada Sisiwa Kelas V di SDN Mustikajaya IV dalam Mengembangkan Potensi Karir dan Cita-Cita Menggunakan Media Kertas Cita-Citaku dan Power Point - Srianita, Yossi; S, Windriani Ulfa; L, Ayuningtyas Nurhayati; Puspita, Hamida; Sari, Wita Puspita (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine how class teachers implement guidance and counseling for students at Mustikajaya IV Elementary School, Bekasi, especially in the application of guidance and counseling services related to developing career potential in students. The research used qualitative methods, literature studies sourced from scientific journals, electronic books, and field studies, namely interviews with fifth grade teachers and conducting student guidance related to careers or ideals. This research focused on the implementation of guidance and counseling services, as well as activities carried out by class teachers. Based on the research findings, class teachers provide counseling guidance services to students such as consultation services, learning services and mediation services or confide in related problems felt by students. This is shown in the analysis results section. In addition, the results show that counseling services in elementary schools play an important role in helping students recognize their talents, interests and potential early on. Classroom teachers, who also act as counselors, facilitate the guidance process through various stages, from collecting student data, identifying talents and interests, to providing career information services. Counseling services that are integrated into learning are able to improve students' self-understanding and readiness in planning for the future. This study recommends strengthening the role of teachers as counselors and developing a systematic career guidance program to support the development of students' career potential in elementary schools.